The role of faculty members in promoting the culture of dialogue in the university environment from the point of view of students at the University of Hafr Al-Batin - Alshuraya, Budur Gasem (Journal of Educational and Psychological Sciences, 2023)
This study aimed to reveal the reality of faculty members’ role in promoting the culture of dialogue in the university environment from the perspective of students at the University of Hafr Al-Batin in Saudi Arabia. To achieve the objectives of the study, the descriptive survey method based on the questionnaire was implemented. The study was applied to a sample of (385) students from the University of Hafr Al-Batin. To collect data, the researcher prepared a questionnaire to explore the reality of university faculty members’ role in promoting the culture of dialogue from the students’ point of view, including four main axes, The results of the study showed that the general mean of the participants’ responses regarding the role of faculty members in promoting a culture of dialogue among students was (3.82), which reflects a "large" level of faculty members’ practice of their roles in developing the culture of dialogue among students. The highest axis was "a faculty member’s perception and understanding of students’ opinions" with a (very large) degree, followed by the axis of "a faculty member’s respect for students and their cultures" with a (large) degree, followed by a topic related to "a faculty member’s commitment to the etiquette of dialogue" with a (large) degree, and the axis of “faculty member encouraging students to engage in collective dialogue” ranked fourth and last as with a (medium) degree.The results also highlighted that there is not statistical significance in the responses of the participants regarding the role of faculty members in promoting the culture of dialogue according to the variables of gender and college.